Sufi Healing and the Translation of Metafunction in Al-Hikam Aphorisms - Muhammad Yunus Anis; Mangatur Nababan; Riyadi Santosa; Moh. Masrukhi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Studies related to Sufi healing have focused on the theories used by Hakim abu-Abdullah Moinuddin al-Chishtiyya related to the power of unconditional love to work healing miracles. The aspects contained in his Book of Sufi Healing consequently become the starting point for the elaboration of the Al-Hikam aphorisms, the monumental work of Ibn Athaillah As-Sakandari. This study aimed to find common ground between Sufi healing and the Al-Hikam aphorisms. To find this meeting point, descriptive analysis was carried out from linguistic and cultural perspectives using Functional Systemic Linguistic theory and Ricoeur’s translation theory applied to Arabic (L1) and Bahasa Indonesia and English language text. The main qualitative data were collected from Arabic clauses in the Al-Hikam aphorisms, comprising 435 clauses with a thematic structure derived from 100 Al-Hikam aphorisms. Linguistic theory was used to examine the text in detail from both micro and macro perspectives, the former being used to examine the shift in form and meaning, and the latter to examine the ideology of translation in conveying Sufi healing in the Al-Hikam aphorisms (infinite hermeneutics in translation). The results showed that the clause structure in Arabic can be divided into three main patterns (SVCOMP/entity-oriented, VSCOMP/event-oriented, and SCOMP/verbless sentence structure). In terms of Ricoeur’s infinite hermeneutics, the position of wager was viewed from the lexical meaning of the Al-Hikam aphorisms, while the transformation stage in the model can be applied to the study of Al-Hikam aphorisms as the basis for understanding Sufi healing.